2020
DOI: 10.2196/19297
|View full text |Cite
|
Sign up to set email alerts
|

Agile Requirements Engineering and Software Planning for a Digital Health Platform to Engage the Effects of Isolation Caused by Social Distancing: Case Study

Abstract: Background Social distancing and shielding measures have been put in place to reduce social interaction and slow the transmission of the coronavirus disease (COVID-19). For older people, self-isolation presents particular challenges for mental health and social relationships. As time progresses, continued social distancing could have a compounding impact on these concerns. Objective This project aims to provide a tool for older people and their families… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 19 publications
0
61
0
3
Order By: Relevance
“…Additionally, our review showed that health chatbots were used in multiple domains. The most prevalent domains were preventive care and risk communication (n=3) ( 3 , 9 , 12 ), public health surveillance by health officials (n=2) ( 2 , 10 ), Telehealth (n=2) ( 1 , 11 ), workplace health and safety (n=1) ( 13 ), and care of the elderly (n=1) ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, our review showed that health chatbots were used in multiple domains. The most prevalent domains were preventive care and risk communication (n=3) ( 3 , 9 , 12 ), public health surveillance by health officials (n=2) ( 2 , 10 ), Telehealth (n=2) ( 1 , 11 ), workplace health and safety (n=1) ( 13 ), and care of the elderly (n=1) ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…Technical features such as speech synthesis from text, data visualization, conversational ability, customization were all vital additions to chatbot applications ( 1 - 3 , 10 - 13 ). Chatbots can be launched from a smartphone-based application (apps) such as LINE, WhatsApp and Telegram ( 10 , 14 ); social media platforms such as Facebook and Twitter ( 3 ); or the developer or service providers’ websites ( 2 , 13 ). Likewise, chatbots can be standalone apps such as the one proposed by Battineni et al ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical frailty can be resolved through educational videos and recorded physical activity sessions (Angulo et al, 2020 ). Actually, online technologies are the most valuable support systems, but have to be appropriately planned for older minds (Meinert et al, 2020 ). Of note, prioritized interventions should be established for low and middle income countries where family dynamics are different, a large number of older adults are illiterate, and proper health care assistance is limited (Lloyd-Sherlock et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…this was really the first time in the history of acute infectious research where ai and machine learning were prominently exploited from the initial discovery of the pathogen onward. in China and elsewhere, new ai-powered smartphone applications (apps) are used to monitor the health of individuals and track the geographical spread of the virus 174 . such apps aim to predict which populations and communities are most susceptible to the negative effects of an infectious disease outbreak, to enable patients to receive real-time information from their medical providers, to provide people with updates about their medical condition without them having to visit a hospital in person and to notify individuals of potential infection hotspots so those areas can be avoided.…”
Section: Box 3 | the Impact Of New Digital Technologiesmentioning
confidence: 99%